Prototype Peternakan Ayam Broiler Berbasis Internet Of Things - selao, ahmad; hidayat, Taufik (Fakultas Teknik Universitas Muhammadiyah Parepare, 2022)
The purpose of making an internet-based broiler chicken prototype system is the formation of a system that can regulate the temperature of the broiler chicken coop automatically by controlling the heating device and also the fan in the closed house-based broiler chicken coop. The other goal is a system that can control the water pump on broiler farms by turning it off automatically according to the condition of the tandom whether it is full or almost empty. In this study, researchers used a descriptive method. This internet of things based broiler farm prototype uses a DHT22 sensor to get the temperature and humidity values and also uses an ultrasonic sensor to get the water level value in the broiler farm air tank. As well as using Nodemcu ESP32 as a data processor and also using firebase cloud as a database. Based on the test, the resulting system can run well with an error rate for Ultrasonic sensors of 0.02% after 6 tests, for DHT22(temperature) sensors of 2.36% after 5 times of testing, for DHT22(humidity) sensors of 7 times. ,55% after 5 times of testing